2006
DOI: 10.1007/s11256-006-0034-6
|View full text |Cite
|
Sign up to set email alerts
|

“Doing the Best We Could”: African American Teachers’ Counterstory on School Desegregation

Abstract: National narratives on the movement to desegregate Southern schools, as construed by dominant cultural forces, focus on school desegregation from the vantage point of dominant culture; portraying school desegregation as a singular and inevitable event emanating from jurisprudence and principles of democracy, with little attention to the complexities of those most impacted. This article argues the importance of including counterstory to such narratives, specifically highlighting the narratives of African Americ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 27 publications
(28 reference statements)
0
15
0
Order By: Relevance
“…These ''other mothers'' were critical in African families and communities because no child was neglected or unsupervised. More recently, works by Dingus (2006), Hughes (2006), Morris and Morris (2002), and Walker (1996) describe how African American teachers in the pre-Brown South cared for their students in spite of the obstacles and challenges imposed by segregation.…”
Section: Teachers Of Color Serve As Role Models For All Studentsmentioning
confidence: 99%
“…These ''other mothers'' were critical in African families and communities because no child was neglected or unsupervised. More recently, works by Dingus (2006), Hughes (2006), Morris and Morris (2002), and Walker (1996) describe how African American teachers in the pre-Brown South cared for their students in spite of the obstacles and challenges imposed by segregation.…”
Section: Teachers Of Color Serve As Role Models For All Studentsmentioning
confidence: 99%
“…We have, however, drawn upon a substantial body of literature to substantiate LaVerne's memories, thoughts, and feelings. We acknowledge that others have desegregated schools in different parts of the country, and their experiences were most likely different, yet as Dingus (2006) pointed out, it is important for individual or minority voices to be heard in the discussion regarding school desegregation. ''Narratives of African American teachers, students, and parents provide counter-story, perspectives that challenge, expand and de-center national narratives as the exclusive domain of dominant cultural forces, accounting for the experiences of those closely related and most impacted by school desegregation'' (p. 213).…”
Section: Resultsmentioning
confidence: 99%
“…She was elected by her fellow students to serve as student council president and she felt valued by her teachers. Dingus (2006) found that African American teachers during the time of segregation were considered to be human resources to their students. Dixon (2003) also found African American educators to teach the whole studentas opposed to the subject-and were considered as being compassionate about their students.…”
Section: Resultsmentioning
confidence: 99%
“…D. Anderson 1988;Bond 1994;Dingus 2006;Fairclough 2001;Foster 1990Foster , 1993Foster , 1997Franklin 2009;Fultz 1995;Kelly 2010; V. G. Morris 2000, 2002;Preston-Grimes 2010;Sherer 1977;Siddle Walker 1996Tillman 2004aTillman , 2004b. Black Southern women educators during this era, in particular, promoted positive images of Blacks in a White supremacist culture, instilled a strong sense of racial pride in their students, and spearheaded efforts to liberate Blacks through literacy (Collier-Thomas and Franklin 2001;Dingus 2006;Harley 1982;Johnson 2000Johnson , 2010A. D. Morris 1984;Neverdon-Morton 1982;Norwood 1998;Perkins 1983Perkins , 1989Shaw 1996).…”
Section: New Directions For Research On Black Education In the Us Southmentioning
confidence: 99%